Find the sum of the series and show your process for finding each term leading to the final sum.


GOT TO SHOW YOUR STEP BY STEP WORK.

Find the sum of the series and show your process for finding each term leading to the final sumGOT TO SHOW YOUR STEP BY STEP WORK class=

Respuesta :

Answer:

[tex]\sum_{k=3}^5(-2k+5)=-9[/tex]

Step-by-step explanation:

The given series is:

[tex]\sum_{k=3}^5(-2k+5)[/tex]

The series is not very lengthy so we can write the expanded form;

[tex]\sum_{k=3}^5(-2k+5)=(-2(3)+5)+(-2(4)+5)+(-2(5)+5)[/tex]

This implies that;

[tex]\sum_{k=3}^5(-2k+5)=-1+-3+-5[/tex]

[tex]\sum_{k=3}^5(-2k+5)=-9[/tex]

ACCESS MORE